Stratification of the lexicon in the work of Muhamed Abdagić - Šehović Aida (Univerzitetska Misao)
The lexicon is an important part of a writer's style and can contribute to the atmosphere, characterization of characters, and description of the environment. Through his choice of lexicon, the writer can express his creativity, and stylistic expression, and also influence the reader. This work aims to present and discuss the lexicon characteristic of the language of Muhamed Abdagić, with an emphasis on highlighting and classifying marked types of that lexicon. Given the goal, the most appropriate methods used are research, analytical, deductive, and illustrative. The results show that the lexicon used by the characters influenced Abdagić's entire work, such that the culture of life, as well as the place and origin of the Bosniaks in Sandžak, are represented in them. These results lead to the conclusion that the lexicon used by the writer is an important indicator of the social, cultural, and regional identity of a nation.